Collective action tribes, empires, nations, and protest movements - Jordan, Bill 1941- (Routledge, Taylor & Francis Group, 2023)
Introduction -- History and Dynamics of Collective Action -- Relationship: The Dynamics of Feeling -- Couples and Families -- Well-being and Social Value -- Civic Relationships and Civil Society -- Globalisation -- Conflict and Coercion -- A New Direction? -- The Revival of Nationalism -- The State -- Mobility and Migration -- Extremism, Political and Religious -- Nations and Sustainability -- A New Cold War? -- Possible Alternatives -- Conclusions.
Includes bibliographical references and index
Keywords: Kollektives Handeln; Zivilgesellschaft; Soziale Bewegung; Interpersonal relations; Social interaction; Civil society